Unemployment duration, aggregate demand and unemployment-insurance - a study of irish live register survival probabilities, 1967-1978 - Hughes, G; Walsh, Bm (Economic & Social Studies, 1983)
Abstract: Quarterly data on the duration of unemployment for males and females are used to derive measures of the probability of remaining on the live Register for another quarter for persons who have been on the register for very short, short, medium, and long durations. A logit transformation is applied to the survival probabilities and a general model of unemployment is tested to see if it can account for variations in the probability of remaining unemployed for these four duration categories during the period 1967-78. Regression results suggest that the survival probabilities are responsive to changes in the maximum period for which unemployment benefits are payable and to changes in labour market conditions. The results are used to derive the survival probabilities which would have obtained if there had been no change in the unemployment insurance (UI) variables. These hypothetical values are used in conjunction with the actual values within a demographic projection framework to estimate the effects which changes in the UI variables may have on the steady state level of the Live Register.
Keywords: Economics; Sociology